Use of Conjunctions in Chinese and Uzbek Languages - Tojiboyev Islom Odil o`g`li (International Journal on Integrated Education, 2021)
This article provides a general description of the conjunctions that are considered important in language, their use, what functions they perform in speech, and brief explanations and examples of some of them.